Quantifying the effect of corrective surgery for trigonocephaly: A non-invasive, non-ionizing method using three-dimensional handheld scanning and statistical shape modelling. Issue 3 (March 2017) - Rodriguez-Florez, Naiara; Göktekin, Özge K.; Bruse, Jan L.; Borghi, Alessandro; Angullia, Freida; Knoops, Paul G.M.; Tenhagen, Maik; O'Hara, Justine L.; Koudstaal, Maarten J.; Schievano, Silvia; Jeelani, N.U. Owase; James, Greg; et al.
Abstract: Trigonocephaly in patients with metopic synostosis is corrected by fronto-orbital remodelling (FOR). The aim of this study was to quantitatively assess aesthetic outcomes of FOR by capturing 3D forehead scans of metopic patients pre- and post-operatively and comparing them with controls. Ten single-suture metopic patients undergoing FOR and 15 age-matched non-craniosynostotic controls were recruited at Great Ormond Street Hospital for Children (UK). Scans were acquired with a three-dimensional (3D) handheld camera and post-processed combining 3D imaging software. 3D scans were first used for cephalometric measurements. Statistical shape modelling was then used to compute the 3D mean head shapes of the three groups (FOR pre-op, post-op and controls). Head shape variations were described via principal component analysis (PCA). Cephalometric measurements showed that FOR significantly increased the forehead volume and improved trigonocephaly. This improvement was supported visually by pre- and post-operative computed mean 3D shapes and numerically by PCA (p < 0.001). Compared with controls, post-operative scans showed flatter foreheads (p < 0.001). In conclusion, 3D scanning followed by 3D statistical shape modelling enabled the 3D comparison of forehead shapes of metopic patients and non-craniosynostotic controls, and demonstrated that the adopted FOR technique was successful in correcting bitemporal narrowing but overcorrected the rounding of the forehead.